2022
DOI: 10.7759/cureus.27869
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Synergistic Effects of Tea Tree Oil and Neem Extract on Candida albicans Adhesion to Denture Soft Liner

Abstract: BackgroundInflammation is present in denture stomatitis. Denture stomatitis's etiology is complex, but there is evidence that it is brought on by Candida albicans growing in biofilms on its surface. ObjectiveThis study aimed to examine and assess the effectiveness of several herbal products, such as tea tree oil and neem extracts, on Candida albicans adhesion to denture soft liners. MethodEach wall of the tissue culture plate was filled with 30 acrylic blocks lined with soft liners, followed by the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Many studies have found that TTO can inhibit LPS- [ 14 , 15 ], bacteria- [ 16 ], and Indiana vesiculovirus- [ 17 ] induced host cell inflammation. TTO has diverse components, which mainly include T-4-O, γ-terpinene, α-terpineol, and 1,8-cineole [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that TTO can inhibit LPS- [ 14 , 15 ], bacteria- [ 16 ], and Indiana vesiculovirus- [ 17 ] induced host cell inflammation. TTO has diverse components, which mainly include T-4-O, γ-terpinene, α-terpineol, and 1,8-cineole [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its antifungal effect has been demonstrated in several investigations [ 98 , 99 ]. Exposing the DBR samples to neem extract was found effective in minimizing the adherence of C. albicans [ 100 ]. In a recent investigation, neem powder was incorporated into heat and auto-polymerized DBR at 0.5, 1, 1.5, 2, and 2.5 wt.% [ 67 ].…”
Section: Methods Used For Tuning Bioactive and Antimicrobial Dbr Mate...mentioning
confidence: 99%
“…Each culture plate was incubated for 72 hours at 37° C andthe number of colony forming unit in each plate of each disinfectant at various dilutions were measured using a digital colony counter (10DCC01 DBK digital colony counter, India).The values were expressed as number of colonies forming units per mL(CFU/mL). 12…”
Section: Adherence Testingmentioning
confidence: 99%